THE COLONIZATION TRIAL POLICY IN GEDONG TATAAN, LAMPUNG IN 1905-1917 (Paramita: Historical Studies Journal, 2018)
The problem of colonization policy in Gedong Tataan (South Sumatera) made the main theme in this research is to know one part of Dutch colonial politics in the Dutch East Indies in the modern imperative era in the first half of the 20th century. The policy is an implementation of one of the ethical political programs, namely: the emigration proclaimed by the Dutch in 1901, which would implicitly be used for the welfare of the Indies population. However, in practice, the colonization was then politicized by the Dutch who conspired with the private capitalists, to expand the exploitation of natural resources and labor to the Outer Islands region. Since the problem of this research has taken place in the past, the archives of the Dutch colonial archives, books, journals and newspapers related to the theme of this research are used as sources in this dissertation; and the analysis of this study uses a critical historical method in order to obtain a reconstruction of the history of colonization that is close to the truth. In conclusion, the policy of colonization in Gedong Tataan was the Dutch colonial ambition or politics to improve the welfare of the native population, and as a pioneer for the procurement of labor or private capital of the capitalist plantations outer Java. Â Â Kajian tentang kebijakan kolonisasi di Gedong Tataan (wilayah Sumatera Selatan) bertujuan untuk mengetahui salah satu bagian dari politik kolonial Belanda di Hindia Belanda di jaman imperliasme modern pada paruh pertama abad ke-20. Kebijakan itu merupakan suatu implementasi dari salah satu program politik etis, yaitu: emigrasi yang dicanangkan oleh Belanda pada tahun 1901, yang secara implisit akan digunakan untuk kesejahteraan penduduk bumiputera Hindia Belanda. Akan tetapi, di dalam praktiknya kolonisasi itu kemudian dipolitisasi oleh Belanda yang berkonspirasi dengan para pemilik modal swasta (kapitalis), untuk memperluas eksploitasi sumber daya alam dan tenaga kerja ke daerah kepulauan di Luar Jawa. Oleh karena, masalah penelitian ini telah terjadi di masa lampau, maka bahan-bahan arsip kolonial Belanda, buku, jurnal, dan surat kabar yang terkait dengan tema digunakan sebagai sumber dalam penelitian ini. Analisis penelitian ini menggunakan metode sejarah kritis agar dapat diperoleh rekonstruksi sejarah kolonisasi yang mendekati dengan kebenaran. Sebagai kesim-pulan, bahwa kebijakan kolonisasi di Gedong Tataan itu merupakan ambisi atau politik kolonial Belanda untuk meningkatkan kesejahteraan penduduk bumiputera, dan sebagai pionir untuk pengadaan tenaga kerja atau kuli-kuli perkebunan swasta kaum kapitalis di Luar Jawa.Â